New Technologies of the Development of a Code of Bioethics - Alexandr Anatolievich Mokhov; Yury Alexandrovich Svirin; Vladimir Aleksandrovich Gureev; Natalya Semenovna Posulikhina; Alexey Victorovich Pekshev (Institute of Medico-legal Publications Pvt Ltd, 2021)
The article examines the main challenges and threats to humankind caused by the New TechnologicalRevolution. Due to the development of genetic, information, and other technologies closely related topersonal and family data and the intervention of state and society into the physical and spiritual spheres ofindividuals and families, a significant role in making political, managerial, and other decisions is playedby civil society institutions. This includes procedures for the ethical and legal assessment (examination) ofnew technologies. During the rapid development of bioeconomics and the digital economy, both traditional(legislative norms) and non-traditional (norms of ethics, bioethics, and ethics of high technology) sourcesof law are gaining importance. In Russia, the issues of legal and ethical support for scientific, innovative,and other types of economic activity are still being formed. Following the path of innovative development,several developed economies adopted legal norms, legal institutions, and special laws to implement nationalbiopolicies. Methods: The authors of the article used general scientific methods (sociological, systemic,structural, and functional), the method of theoretical analysis, and special scientific methods (comparativelegaland technical-legal analysis, specification, and interpretation). The methodological basis of the researchwas laid by the theory of knowledge. Objective: The article aims to substantiate the need to adopt a Codeof Bioethics. This document should determine the foundations of biopolitics, its basic principles, objects,structures, and other constitutive features (characteristics). Results: The study has substantiated the need fordeveloping and adopting the Law “On Bioethics” and, subsequently, the Code of Bioethics.